A method for preparing a reconstructed LDH catalyst for photoanode water splitting

By introducing reconstituted LDH catalysts, including NiFe-LDH and FeOOH films, and using Ag@SiO2 nanoparticles, the problem of low photogenerated carrier separation efficiency and transfer efficiency is solved, significantly improving PEC-WS performance.

CN115386898BActive Publication Date: 2025-03-11ANYANG NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211085249.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-06
Publication Date
2025-03-11
Estimated Expiration
2042-09-06

AI Technical Summary

Technical Problem

The photogenerated carrier separation efficiency and transfer efficiency of metal oxide semiconductor photoelectrodes are low, which limits the improvement of photoelectrochemical decomposition water (PEC-WS) performance.

Method used

Using the preparation method of reconstituted LDH catalyst, NiFe-LDH was introduced through hydrothermal synthesis, and FeOOH film was introduced by electrodeposition method, combining the plasmon effect of Ag@SiO2 nanoparticles, the carrier separation and transfer efficiency of oxide thin film photoelectrode was improved.

Benefits of technology

The charge transfer efficiency of the photoanode surface is significantly improved, the PEC-WS performance of α-Fe2O3 is enhanced, the stability of the catalyst is improved, and the interface defect is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115386898B_ABST
    Figure CN115386898B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a reconstructed LDH catalyst for photoanode water splitting, comprising the following steps: S1, washing an FTO substrate; S2, preparing a solution; S3, preparing an FTO / FeOOH sample; S4, preparing FTO / Sn@FeOOH; S5, preparing FTO / Sn@α-Fe 2 O 3 Preparation of S6, FTO / Sn@α‑Fe 2 O 3 / Ni 3 Preparation of FeOOH; S7, FTO / Sn@α‑Fe 2 O 3 / Ni 3 FeOOH / Ag@SiO 2 / FeOOH photoanode; NiFe‑LDH was introduced by hydrothermal synthesis, and FeOOH was introduced by electrodeposition to improve the stability of NiFe‑LDH catalyst. 2 The plasmon effect of nanoparticles reduces interface defects and significantly improves the performance of PEC‑WS.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of LDH catalyst preparation methods, and in particular relates to a preparation method of a reconstructed LDH catalyst for photoanode water splitting. Background Art

[0002] With the increasing consumption of fossil fuels and greenhouse gas emissions, the development of new sustainable energy technologies is urgent. Photoelectrochemical water splitting (PEC-WS) is a process that converts and stores solar energy, providing a promising strategy for the production of renewable hydrogen fuels and environmental remediation. The PEC-WS system can use semiconductor photoelectric materials to achieve water splitting with the help of solar radiation. The key lies in finding suitable semiconductor photoanode materials. Metal oxide semiconductors have attracted widespread attention due to their good chemical stability, abundant resources and easy preparation. However, the separation efficiency and transfer efficiency of photogenerated carriers of metal oxide semiconductor photoelectrodes are generally low, which has a serious limiting effect on the improvement of PEC-WS performance. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a reconstructed LDH catalyst for photoanode water splitting, using the LDH catalyst to modify the oxide thin film photoanode to improve the carrier separation and transfer efficiency of the oxide thin film photoelectrode.

[0004] The present invention provides the following technical solutions:

[0005] A method for preparing a reconstructed LDH catalyst for photoanode water splitting comprises the following steps:

[0006] S1. FTO substrate washing: The FTO substrate was washed with acetone, ethanol and deionized water for 15 minutes each in sequence;

[0007] S2, solution preparation: FeCl3 and urea are mixed, dissolved with deionized water, and placed in a polytetrafluoroethylene-lined container;

[0008] S3, FTO / FeOOH sample preparation: Place the washed FTO substrate obliquely into the mixed solution prepared in step S2, and heat it in a constant temperature box at 80-120°C for 10-14 hours, and cool it after heating;

[0009] S4. Preparation of FTO / Sn@FeOOH: After cooling, the synthesized FTO / FeOOH sample was taken out, washed with deionized water, and immersed in SnCl4 ethanol solution for 8-12 minutes to obtain FTO / Sn@FeOOH;

[0010] S5. Preparation of FTO / Sn@α-Fe2O3: After washing FTO / Sn@FeOOH with deionized water, drying at 40-80 °C, and annealing at 400-600 °C and 650-710 °C for 1-3 hours and 10-20 minutes, respectively, to obtain FTO / Sn@α-Fe2O3;

[0011] S6. Preparation of FTO / Sn@α-Fe2O3 / Ni3FeOOH: The synthesized FTO / Sn@α-Fe2O3 was placed in a polytetrafluoroethylene reactor, and then a mixed aqueous solution containing Ni(NO3)2, Fe(NO3)3 and urea was added, and the mixture was reacted at 80-120 °C for 4-8 hours to obtain FTO / Sn@α-Fe2O3 / Ni3FeOOH;

[0012] S7. Preparation of FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode: spin-coat the Ag@SiO2 solution on the surface of the FTO / Sn@α-Fe2O3 / Ni3FeOOH film, dry it at 40-80 ℃ for 20-40 minutes, and obtain the FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode by electrodeposition.

[0013] Preferably, in step S7, the electrodeposition method is to carry out electrodeposition in a three-electrode system, wherein Pt is a counter electrode, an Ag / AgCl electrode is a reference electrode, and an 80-120 mL solution containing FeCl3, NH4F, KCl, and H2O2 is used as an electrolyte solution. The electrodeposition adopts cyclic voltammetry, and the scanning voltage range is -0.49 V~0.41 V, the scanning rate is 100 m V / s, and the scanning turns are 4-6 times, thereby obtaining a FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode.

[0014] Preferably, in step S2, the molar ratio of FeCl3 to urea is 1:1, and the volume of the deionized water is 50 mL.

[0015] Preferably, in step S3, the washed FTO substrate is placed in the mixed solution prepared in step S2 at an angle of 45 degrees, and heated in a 100° C. thermostat for 12 hours, and then cooled after heating.

[0016] Preferably, in S5, the preparation of FTO / Sn@α-Fe2O3 is to wash FTO / Sn@FeOOH with deionized water, dry it at 60°C, and then anneal it at 500°C and 680°C for 2 hours and 15 minutes respectively to obtain FTO / Sn@α-Fe2O3.

[0017] Preferably, in step S6, the molar ratio of Ni(NO3)2, Fe(NO3)3 and urea in the mixed aqueous solution containing Ni(NO3)2, Fe(NO3)3 and urea is (2.8-3.1):(0.8-1.2):(1.8-2.2).

[0018] Preferably, LDHs with different Ni-Fe ratios are synthesized, and the number of electrodeposition cycles is adjusted to improve the photoanode material, thereby obtaining an oxide thin film photoanode material with optimal performance.

[0019] The present invention also discloses a reconstructed LDH catalyst prepared by a preparation method of a reconstructed LDH catalyst for photoanode water splitting. The catalyst comprises, from bottom to top, an FTO substrate, an oxide film, a NiFe-LDH film, Ag@SiO2 particles, and a FeOOH film.

[0020] Preferably, the oxide film is any one of α-Fe2O3, TiO2, WO3, Cu2O, and BiVO4.

[0021] Preferably, the NiFe-LDH has a thickness of 90-110 nm.

[0022] Preferably, the oxide film has a thickness of 450-550 nm, the Ag@SiO2 is a uniform nanoparticle with a diameter of 45-55 nm, and the FeOOH has a uniform thickness of 4-6 nm.

[0023] Preferably, the reconstructed LDH catalyst is used in the application of photoanode in photolysis of water.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention provides a method for preparing a reconstructed LDH catalyst for photoanode water splitting, wherein NiFe-LDH is introduced by a hydrothermal synthesis method, and FeOOH is introduced by an electrodeposition method, thereby improving the stability of the NiFe-LDH catalyst, reducing interface defects by means of the plasmon effect of Ag@SiO2 nanoparticles, and significantly improving the performance of PEC-WS.

[0026] (2) The present invention discloses a method for preparing a reconstructed LDH catalyst for photoanode water splitting. The Sn-doped α-Fe2O3 photoelectrode is synthesized by hydrothermal synthesis and high temperature annealing. The PEC-WS performance is improved by synthesizing LDH with different Ni-Fe ratios and adjusting the number of electrodeposition cycles. The α-Fe2O3 thin film photoanode material of the target LDH is synthesized by continuously growing five cycles of FeOOH films. The charge transfer efficiency on the photoanode surface is significantly improved, and the PEC-WS performance of α-Fe2O3 is significantly enhanced.

[0027] (3) The present invention discloses a method for preparing a reconstructed LDH catalyst for photoanode water splitting, which utilizes FeOOH film to improve the instability of NiFe-LDH catalyst in the process of photoanode water splitting, and utilizes Ag@SiO2 metal nanoparticles to modify the interface, thereby improving the slow oxygen absorption reaction kinetics and interface defects, significantly improving the charge transfer efficiency on the oxide photoanode surface, and significantly enhancing the photoanode water splitting performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 :Schematic diagram of the structure of reconstructed LDH catalyst for hematite film photoanode;

[0030] Figure 2 :SEM top view of FTO / Sn@α-Fe2O3 photoanode;

[0031] Figure 3 :SEM top view of FTO / Sn@α-Fe2O3 / Ni3FeOOH photoanode;

[0032] Figure 4 : Scanning electron microscopy (SEM) top view of FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 photoanode;

[0033] Figure 5 : Scanning electron microscopy (SEM) top view of FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode;

[0034] Figure 6 : Ultraviolet-visible absorption (UV-vis) spectrum of the photoanode;

[0035] Figure 7 : X-ray diffraction (XRD) spectrum of the photoanode;

[0036] Figure 8 : JV diagrams of the photoelectrode under different bias voltages;

[0037] Fig. 9 : JV diagrams of the photoelectrode under different bias voltages;

[0038] Fig.10: JV diagrams of the photoanode under different bias voltages;

[0039] Fig.11 : Transient photocurrent density (it) diagram;

[0040] Fig.12 :Photoelectric conversion efficiency spectrum of photoanode under different bias voltages;

[0041] Fig.13 : Photoelectrode at 1.2 V RHE Photoelectrochemical impedance spectroscopy;

[0042] Fig.14 : DFT calculation of local electrostatic potential spectrum of photoanode. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Embodiment 1:

[0046] A method for preparing a reconstructed LDH catalyst for photoanode water splitting comprises the following steps:

[0047] S1. FTO substrate washing: The FTO substrate was washed with acetone, ethanol and deionized water for 10 minutes each in sequence;

[0048] S2, solution preparation: 4.5 mmol of FeCl3 and 4.5 mmol of urea were mixed and dissolved with 50 mL of deionized water and placed in a 100 mL polytetrafluoroethylene-lined container;

[0049] S3, FTO / FeOOH sample preparation: the washed FTO substrate is placed in the mixed solution prepared in step S2 at an angle of 45°, and heated in a constant temperature box at 80°C for 10 hours, and then cooled after heating;

[0050] S4. Preparation of FTO / Sn@FeOOH: After cooling, the synthesized FTO / FeOOH sample was taken out, washed with deionized water, and immersed in 0.1 mol / L SnCl4 ethanol solution for 8 minutes to obtain FTO / Sn@FeOOH;

[0051] S5, preparation of FTO / Sn@α-Fe2O3: FTO / Sn@FeOOH was washed with deionized water, dried at 40 °C, and then annealed at 400 °C and 650 °C for 1 hour and 10 minutes respectively to obtain FTO / Sn@α-Fe2O3;

[0052] S6, preparation of FTO / Sn@α-Fe2O3 / Ni3FeOOH: The synthesized FTO / Sn@α-Fe2O3 was placed in a polytetrafluoroethylene reactor, and then 60 mL of a mixed aqueous solution containing 1.26 mmol of Ni(NO3)2, 0.42 mmol of Fe(NO3)3 and 8.4 mmol of urea was added, and the mixture was reacted at 80 °C for 4 hours to obtain FTO / Sn@α-Fe2O3 / Ni3FeOOH;

[0053] S7. Preparation of FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode: The Ag@SiO2 solution was spin-coated on the surface of the FTO / Sn@α-Fe2O3 / Ni3FeOOH film, dried at 40 °C for 20 min, and electrodeposited in a three-electrode system, where Pt was the counter electrode, the Ag / AgCl electrode was the reference electrode, and 100 mL of a solution containing 2.5 mmol of FeCl3, 2.5 mmol of NH4F, 0.05 mmol of KCl, and 1.5 mL of H2O2 was used as the electrolyte solution. The electrodeposition was carried out by cyclic voltammetry with a scanning voltage range of -0.49 V~0.41 V, a scanning rate of 100 mV / s, and a scanning number of 5 times. Thus, the FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode was obtained.

[0054] Embodiment 2

[0055] A method for preparing a reconstructed LDH catalyst for photoanode water splitting comprises the following steps:

[0056] S1. FTO substrate washing: The FTO substrate was washed with acetone, ethanol and deionized water for 15 minutes each in sequence;

[0057] S2, solution preparation: 4.5 mmol of FeCl3 and 4.5 mmol of urea were mixed and dissolved with 50 mL of deionized water and placed in a 100 mL polytetrafluoroethylene-lined container;

[0058] S3, FTO / FeOOH sample preparation: Place the washed FTO substrate at an angle of 45° into the mixed solution prepared in step S2, and heat it in a 100°C constant temperature oven for 12 hours, and cool it after heating;

[0059] S4. Preparation of FTO / Sn@FeOOH: After cooling, the synthesized FTO / FeOOH sample was taken out, washed with deionized water, and immersed in 0.1 mol / L SnCl4 ethanol solution for 10 minutes to obtain FTO / Sn@FeOOH;

[0060] S5, preparation of FTO / Sn@α-Fe2O3: FTO / Sn@FeOOH was washed with deionized water, dried at 60 °C, and then annealed at 500 °C and 680 °C for 2 hours and 15 minutes, respectively, to obtain FTO / Sn@α-Fe2O3;

[0061] S6, preparation of FTO / Sn@α-Fe2O3 / Ni3FeOOH: The synthesized FTO / Sn@α-Fe2O3 was placed in a polytetrafluoroethylene reactor, and then 60 mL of a mixed aqueous solution containing 1.26 mmol of Ni(NO3)2, 0.42 mmol of Fe(NO3)3 and 8.4 mmol of urea was added, and the mixture was reacted at 100 °C for 6 hours to obtain FTO / Sn@α-Fe2O3 / Ni3FeOOH;

[0062] S7. Preparation of FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode: The Ag@SiO2 solution was spin-coated on the surface of the FTO / Sn@α-Fe2O3 / Ni3FeOOH film, dried at 60 °C for half an hour, and electrodeposited in a three-electrode system, where Pt was the counter electrode, the Ag / AgCl electrode was the reference electrode, and 100 mL of a solution containing 2.5 mmol of FeCl3, 2.5 mmol of NH4F, 0.05 mmol of KCl, and 1.5 mL of H2O2 was used as the electrolyte solution. The electrodeposition was carried out by cyclic voltammetry with a scanning voltage range of -0.49 V~0.41 V, a scanning rate of 100 mV / s, and a scanning number of 5 times. Thus, the FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode was obtained.

[0063] Embodiment 3

[0064] A method for preparing a reconstructed LDH catalyst for photoanode water splitting comprises the following steps:

[0065] S1. FTO substrate washing: The FTO substrate was washed with acetone, ethanol and deionized water for 20 minutes each in sequence;

[0066] S2, solution preparation: 4.5 mmol of FeCl3 and 4.5 mmol of urea were mixed and dissolved with 50 mL of deionized water and placed in a 100 mL polytetrafluoroethylene-lined container;

[0067] S3, FTO / FeOOH sample preparation: the washed FTO substrate is placed in the mixed solution prepared in step S2 at an angle of 45°, and heated in a 120°C constant temperature box for 14 hours, and then cooled after heating;

[0068] S4. Preparation of FTO / Sn@FeOOH: After cooling, the synthesized FTO / FeOOH sample was taken out, washed with deionized water, and immersed in 0.1 mol / L SnCl4 ethanol solution for 12 min to obtain FTO / Sn@FeOOH;

[0069] S5, preparation of FTO / Sn@α-Fe2O3: FTO / Sn@FeOOH was washed with deionized water, dried at 80 °C, and then annealed at 500 °C and 680 °C for 3 hours and 20 minutes, respectively, to obtain FTO / Sn@α-Fe2O3;

[0070] S6, preparation of FTO / Sn@α-Fe2O3 / Ni3FeOOH: The synthesized FTO / Sn@α-Fe2O3 was placed in a polytetrafluoroethylene reactor, and then 60 mL of a mixed aqueous solution containing 1.26 mmol of Ni(NO3)2, 0.42 mmol of Fe(NO3)3 and 8.4 mmol of urea was added, and the mixture was reacted at 120 °C for 8 hours to obtain FTO / Sn@α-Fe2O3 / Ni3FeOOH;

[0071] S7. Preparation of FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode: The Ag@SiO2 solution was spin-coated on the surface of the FTO / Sn@α-Fe2O3 / Ni3FeOOH film, dried at 80 °C for 40 min, and electrodeposited in a three-electrode system, where Pt was the counter electrode, the Ag / AgCl electrode was the reference electrode, and 100 mL of a solution containing 2.5 mmol of FeCl3, 2.5 mmol of NH4F, 0.05 mmol of KCl, and 1.5 mL of H2O2 was used as the electrolyte solution. The electrodeposition was carried out by cyclic voltammetry with a scanning voltage range of -0.49 V~0.41 V, a scanning rate of 100 mV / s, and a scanning number of 5 times. Thus, the FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode was obtained.

[0072] Embodiment 4

[0073] A reconstructed LDH catalyst prepared by a preparation method for a reconstructed LDH catalyst for photoanode water splitting, the catalysts are, from bottom to top: FTO substrate, oxide film, NiFe-LDH film, Ag@SiO2 particles, FeOOH film.

[0074] The oxide film is any one of α-Fe2O3, TiO2, WO3, Cu2O, and BiVO4, the NiFe-LDH has a thickness of 90-110 nm, the oxide film has a thickness of 450-550 nm, the Ag@SiO2 is a uniform nanoparticle with a diameter of 45-55 nm, and the FeOOH has a uniform thickness of 4-6 nm.

[0075] Embodiment 5

[0076] A reconstructed LDH catalyst prepared by a preparation method for a reconstructed LDH catalyst for photoanode water splitting, the catalysts are, from bottom to top: FTO substrate, oxide film, NiFe-LDH film, Ag@SiO2 particles, FeOOH film.

[0077] The oxide film is any one of α-Fe2O3, TiO2, WO3, Cu2O, and BiVO4, the NiFe-LDH thickness is 90 nm, the oxide film thickness is 450 nm, the Ag@SiO2 is uniform nanoparticles with a diameter of 45 nm, and the FeOOH is uniform in thickness of 4 nm.

[0078] Embodiment 6

[0079] A reconstructed LDH catalyst prepared by a preparation method for a reconstructed LDH catalyst for photoanode water splitting, the catalysts are, from bottom to top: FTO substrate, oxide film, NiFe-LDH film, Ag@SiO2 particles, FeOOH film.

[0080] The oxide film is any one of α-Fe2O3, TiO2, WO3, Cu2O, and BiVO4, the NiFe-LDH has a thickness of 100 nm, the oxide film has a thickness of 500 nm, the Ag@SiO2 is a uniform nanoparticle with a diameter of 50 nm, and the FeOOH has a uniform thickness of 5 nm.

[0081] Embodiment 7

[0082] A reconstructed LDH catalyst prepared by a preparation method for a reconstructed LDH catalyst for photoanode water splitting, the catalysts are, from bottom to top: FTO substrate, oxide film, NiFe-LDH film, Ag@SiO2 particles, FeOOH film.

[0083] The oxide film is any one of α-Fe2O3, TiO2, WO3, Cu2O, and BiVO4, the NiFe-LDH thickness is 110 nm, the oxide film thickness is 550 nm, the Ag@SiO2 is uniform nanoparticles with a diameter of 55 nm, and the FeOOH is uniform in thickness with a thickness of 6 nm.

[0084] Embodiment 8

[0085] The reconstructed LDH catalyst is used for photoanode water splitting.

[0086] Embodiment 9

[0087] Figure 1 Schematic diagram of the structure of the reconstructed LDH catalyst for hematite thin film photoanode; where: FTO represents the growth substrate, Sn@α-Fe2O3 represents the oxide film, Ni3FeOOH represents the LDH catalyst, Ag@SiO2 is the metal nanoparticle, and FeOOH is the surface catalyst; Figure 2 This is a top view of the FTO / Sn@α-Fe2O3 photoanode scanning electron microscope (SEM). The SEM image shows that the surface of the FTO / Sn@α-Fe2O3 photoelectrode is stick-shaped; Figure 3 This is a top view of the FTO / Sn@α-Fe2O3 / Ni3FeOOH photoanode scanning electron microscope (SEM), showing that the surface of the Sn@α-Fe2O3 photoelectrode is nanosheet-shaped after the introduction of the Ni3FeOOH film. Figure 4This is a top view of the FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 photoanode scanning electron microscope (SEM). The photoelectrode morphology after surface modification with the introduction of spherical Ag@SiO2 is shown. Figure 5 This is a top view of the FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode scanning electron microscope (SEM). In order to solve the depression in the photocurrent density curve, the FeOOH film was covered on the outermost layer of the sample electrode by electrodeposition. Figure 6 The UV-visible absorption (UV-vis) spectra of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / Ni3FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 and FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanodes show that the absorption spectra of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / Ni3FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 and FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoelectrodes are not much different;

[0088] Figure 7 The X-ray diffraction (XRD) spectra of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / Ni3FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 and FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanodes show no obvious changes in their physical phases;

[0089] Figure 8 FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / NiOOH, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / NiFeOOH, FTO / Sn@α-Fe2O3 / Ni2FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH photoelectrodes under different bias voltages JV Figure: The photocurrent density of NiFe-LDH with different ratios introduced on the surface of Sn@α-Fe2O3 photoelectrode reaches 2.48 mA / cm 2 , compared with the simple FTO / Sn@α-Fe2O3 photoelectrode, Figure 8The photocurrent density of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / NiOOH, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / NiFeOOH, FTO / Sn@α-Fe2O3 / Ni2FeOOH and FTO / Sn@α-Fe2O3 / Ni3FeOOH photoanodes under a certain voltage range was analyzed: after introducing different proportions of NiFe-LDH, the photocurrent density of the photoanode material increased from 0.92 mA / cm 2 Increased to 2.48 mA / cm 2 ; Fig. 9 The photoelectrodes of FTO / Sn@α-Fe2O3 / Ni3FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH / FeOOH-1, FTO / Sn@α-Fe2O3 / Ni3FeOOH / FeOOH-3, FTO / Sn@α-Fe2O3 / Ni3FeOOH / FeOOH-5, and FTO / Sn@α-Fe2O3 / Ni3FeOOH / FeOOH-7 were subjected to different bias voltages. J- V Figure: The photocurrent density of FeOOH with different electrodeposition cycles introduced on the surface of FTO / Sn@α-Fe2O3 / Ni3FeOOH photoelectrode reaches 3.55 mA / cm 2 , compared with the simple FTO / Sn@α-Fe2O3 / Ni3FeOOH photoelectrode, and JV The valley in the curve disappears after the introduction of FeOOH, which greatly improves the stability of the photoanode. Specifically, the photocurrent density of FTO / Sn@α-Fe2O3 / Ni3FeOOH photoelectrode with different electrodeposition cycles at 1.23 VRHE reaches 3.55 mA / cm 2 , its PEC performance has also been significantly improved; Fig.10 FTO / Sn@α-Fe2O3 / Ni3FeOOH / FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag / FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanodes at different bias voltages JV Figure: After Ag and Ag@SiO2 doping modification on the surface of FTO / Sn@α-Fe2O3 / Ni3FeOOH / FeOOH photoelectrode, the photocurrent density reached 4.54 mA / cm 2 , compared with the simple FTO / Sn@α-Fe2O3 / Ni3FeOOH / FeOOH photoelectrode, it is increased by 490%;

[0090] Fig.11The transient photocurrent density (it) diagrams of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / Ni3FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 and FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH show that the attenuation rates of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / Ni3FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 and FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH are 48.5%, 73.6%, 47.4% and 46.2%, respectively; Fig.12 Figure 3: Photoelectric conversion efficiency of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / Ni3FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 and FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanodes at different bias voltages between 0.6 V and 1.2 V. The FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode exhibits the highest conversion efficiency. The ABPE diagrams of the four sample photoelectrodes tested in the range of 0.6 V to 1.2 V show that FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH has the highest conversion efficiency at 1.01 V. RHE The maximum applied potential conversion efficiency is 0.69%. Fig.13 The photoelectrodes of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / Ni3FeOOH, FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 and FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH were tested at 1.2 V. RHE Photoelectrochemical impedance spectroscopy; when Ni3FeOOH, Ag@SiO2, and FeOOH films are introduced on the surface of Sn@α-Fe2O3, the photoelectrode transmission resistance gradually decreases, 1.2 V RHE The photoelectrochemical impedance spectrum shows that the FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoelectrode has the smallest radius, indicating that the introduction of Ni3FeOOH film, Ag@SiO2 particles and FeOOH film can effectively reduce the transmission resistance and increase the efficiency of photogenerated charge transfer. Fig.14: DFT calculated the local electrostatic potential spectrum of the photoanode. FeOOH has a higher electrostatic potential than Ni3FeOOH and α-Fe2O3. After the introduction of FeOOH, an internal electric field from α-Fe2O3 / Ni3FeOOH to FeOOH is formed, which promotes carrier separation.

[0091] The above data fully prove the feasibility of the method for preparing a reconstructed LDH catalyst for photoanode water splitting. Sn-doped α-Fe2O3 photoelectrode was prepared by this scheme, Ni3FeOOH film was prepared by hydrothermal synthesis to increase the photocurrent density intensity of Sn@α-Fe2O3, surface modification was performed with Ag@SiO2 particles, and then a layer of FeOOH film was covered by electrodeposition for 5 circles. It was found that the separation and transfer efficiency of the photoelectrode carriers was significantly enhanced, and the PEC performance was significantly improved. Detailed mechanism studies show that the formation of the valley in the JV curve of FTO / Sn@α-Fe2O3 / Ni3FeOOH is mainly due to the direction of the built-in electric field formed between Ni3FeOOH and α-Fe2O3, which is opposite to the built-in electric field at the solid-liquid interface, resulting in serious carrier recombination. FeOOH has a higher electrostatic potential than Ni3FeOOH and α-Fe2O3. After the introduction of FeOOH, an internal electric field from α-Fe2O3 / Ni3FeOOH to FeOOH is formed, which synergistically promotes the separation of solid-liquid combined carriers. The introduction of Ag@SiO2 can effectively reduce the interface defects caused by the direct contact between Ni3FeOOH and FeOOH. In addition, its plasma effect can further promote carrier transfer.

[0092] The device obtained by the above technical solution is a method for preparing a reconstructed LDH catalyst for photoanode water splitting, in which NiFe-LDH is introduced by hydrothermal synthesis and FeOOH is introduced by electrodeposition. Combined with various characterizations, it is verified that different co-catalyst doping improves the PEC-WS performance of α-Fe2O3: the photocurrent density shows significant changes and greatly improves the charge separation transfer rate and efficiency on the photoanode surface. The present invention takes the use of FeOOH film to improve the stability of NiFe-LDH catalyst as a starting point, and reduces interface defects by means of the plasmon effect of Ag@SiO2 nanoparticles, so as to greatly improve the performance of PEC-WS.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a reconstructed LDH catalyst for photoanode water splitting, characterized in that: The following steps are involved: S1. FTO substrate washing: wash the FTO substrate with acetone, ethanol and deionized water for 10-20 minutes each; S2, solution preparation: FeCl3 and urea are mixed, dissolved with deionized water, and placed in a polytetrafluoroethylene-lined container; S3, FTO / FeOOH sample preparation: Place the washed FTO substrate obliquely into the mixed solution prepared in step S2, and heat it in a constant temperature box at 80-120°C for 10-14 hours, and cool it after heating; S4. Preparation of FTO / Sn@FeOOH: After cooling, the synthesized FTO / FeOOH sample was taken out, washed with deionized water, and immersed in SnCl4 ethanol solution for 8-12 minutes to obtain FTO / Sn@FeOOH; S5. Preparation of FTO / Sn@α-Fe2O3: After washing FTO / Sn@FeOOH with deionized water, drying at 40-80 °C, and annealing at 400-600 °C and 650-710 °C for 1-3 hours and 10-20 minutes, respectively, to obtain FTO / Sn@α-Fe2O3; S6. Preparation of FTO / Sn@α-Fe2O3 / Ni3FeOOH: The synthesized FTO / Sn@α-Fe2O3 was placed in a polytetrafluoroethylene reactor, and then a mixed aqueous solution containing Ni(NO3)2, Fe(NO3)3 and urea was added, and the mixture was reacted at 80-120 °C for 4-8 hours to obtain FTO / Sn@α-Fe2O3 / Ni3FeOOH; S7. Preparation of FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode: spin-coat the Ag@SiO2 solution on the surface of the FTO / Sn@α-Fe2O3 / Ni3FeOOH film, dry it at 40-80 ℃ for 20-40 minutes, and obtain the FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode by electrodeposition.

2. The method for preparing a reconstructed LDH catalyst for photoanode water splitting according to claim 1, characterized in that: In step S7, the electrodeposition method is to perform electrodeposition in a three-electrode system, wherein Pt is a counter electrode, an Ag / AgCl electrode is a reference electrode, and an 80-120 mL solution containing FeCl3, NH4F, KCl, and H2O2 is used as an electrolyte solution. The electrodeposition adopts cyclic voltammetry, and the scanning voltage range is -0.49 V~0.41 V, the scanning rate is 100 mV / s, and the scanning turns are 4-6 times, thereby obtaining a FTO / Sn@α-Fe2O3 / Ni3FeOOH / Ag@SiO2 / FeOOH photoanode.

3. The method for preparing a reconstructed LDH catalyst for photoanode water splitting according to claim 1, characterized in that: In step S2, the molar ratio of FeCl3 to urea is 1:1, and the volume of deionized water is 50 mL.

4. The method for preparing a reconstructed LDH catalyst for photoanode water splitting according to claim 1, characterized in that: In step S3, the washed FTO substrate is placed in the mixed solution prepared in step S2 at an angle of 45 degrees, and heated in a constant temperature box at 100°C for 12 hours, and then cooled after the heating is completed.

5. The method for preparing a reconstructed LDH catalyst for photoanode water splitting according to claim 1, characterized in that: In the preparation of FTO / Sn@α-Fe2O3 in S5, FTO / Sn@FeOOH was washed with deionized water, dried at 60 °C, and then annealed at 500 °C and 680 °C for 2 hours and 15 minutes, respectively, to obtain FTO / Sn@α-Fe2O3.

6. The method for preparing a reconstructed LDH catalyst for photoanode water splitting according to claim 1, characterized in that: In step S6, the molar ratio of Ni(NO3)2, Fe(NO3)3 and urea in the mixed aqueous solution containing Ni(NO3)2, Fe(NO3)3 and urea is 2.8-3.1:0.8-1.2:1.8-2.

2.

7. The reconstructed LDH catalyst prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The catalysts from bottom to top are: FTO substrate, α-Fe2O3 film, NiFe-LDH film, Ag@SiO2 particles, and FeOOH film.

8. A reconstructed LDH catalyst according to claim 7, characterized in that: The NiFe-LDH has a thickness of 90-110 nm.

9. The use of a reconstructed LDH catalyst according to claim 8, characterized in that: The reconstructed LDH catalyst is used in the application of the photoanode in photolysis of water.

Citation Information

Patent Citations

  • NiCoAl-LDH-modified ferric oxide composite photoanode material and preparation method and application thereof

    CN107268021A

  • Co (OH) 2 modified NiAl-LDH / alpha-Fe2O3 composite photo-anode and preparation method thereof

    CN114438515A